2016
DOI: 10.1002/jcp.25303
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Ageing: Targeting the “Purinome” to Promote Osteogenic Differentiation and Bone Repair

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells that can differentiate into bone forming cells. Such ability is compromised in elderly individuals resulting in bone disorders such as osteoporosis, also limiting their clinical usage for cell transplantation and bone tissue engineering strategies. In bone marrow niches, adenine and uracil nucleotides are important local regulators of osteogenic differentiation of MSCs. Nucleotides can be released to the extracellular milieu under both physiological and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 102 publications
1
51
0
Order By: Relevance
“…This finding explains the more modest bone phenotype observed in the A2BRKO mice than, for example, the A2ARKO mice in which there is more marked and diffuse osteopenia associated with enhanced osteoclast formation and Mature osteoblasts isolated from A2BRKO mice produce more calcified matrix, collagen, and alkaline phosphatase than osteoblasts isolated from WT mice-mature osteoblasts were isolated from the long bones of A2BRKO and WT mice, cultured and then stained for a calcified matrix production (Alizarin Red); b collagen deposition (Sirius Red); and c alkaline phosphatase activity (n = 4 experiments performed in duplicate). Data are expressed as mean ± SEM (Student's t test: *p < 0.05; **p < 0.01) function and apparently reduced bone formation by mature osteoblasts in the absence of A2AR stimulation [3,6,8,17]. The effect of A2BR in osteoclast reduction may be due to interference with NF-kB signaling resulting from an increase in intracellular cAMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding explains the more modest bone phenotype observed in the A2BRKO mice than, for example, the A2ARKO mice in which there is more marked and diffuse osteopenia associated with enhanced osteoclast formation and Mature osteoblasts isolated from A2BRKO mice produce more calcified matrix, collagen, and alkaline phosphatase than osteoblasts isolated from WT mice-mature osteoblasts were isolated from the long bones of A2BRKO and WT mice, cultured and then stained for a calcified matrix production (Alizarin Red); b collagen deposition (Sirius Red); and c alkaline phosphatase activity (n = 4 experiments performed in duplicate). Data are expressed as mean ± SEM (Student's t test: *p < 0.05; **p < 0.01) function and apparently reduced bone formation by mature osteoblasts in the absence of A2AR stimulation [3,6,8,17]. The effect of A2BR in osteoclast reduction may be due to interference with NF-kB signaling resulting from an increase in intracellular cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have extensively studied the role of adenosine and its receptors, in particular A1 and A2A receptors in the maintenance of bone homeostasis in both in vivo and in vitro systems, in rodent and human cells [2][3][4][5][6][7][8]. A recent report suggests that adenosine plays little direct role in regulating or maintaining bone homeostasis, based primarily on in vitro studies [17]. This report is clearly inconsistent with both our prior reports and those of others based on both in vitro and in vivo studies [1-8, 10, 11, 13, 14, 18].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that, although commercially available hMSCs are widely used in studies, 31,82,83 continued development using freshly isolated cells to look at the effects of aging populations and changes in the bone-marrow microenvironments will also indeed be important. 84 Intriguingly, recent work in human umbilical cord perivascular stem cell-derived chondrocyte pellets demonstrated that GDF5 enhanced proliferation, but had no effect on the expression of chondrogenic-related genes, 85 therefore suggesting that the effect of GDF5 may also be stem/stromal cell source specific.…”
Section: Discussionmentioning
confidence: 99%
“…An increased expression of NTPDases1, ‐2, and ‐3 was found in differentiating postmenopausal bone marrow MSCs at later maturation stages of in vitro cultures. This resulted in a lowered level of MSC osteogenesis and decreased mineralization in cells obtained from postmenopausal women when compared with cells isolated from young females (Noronha‐Matos & Correia‐de‐Sá, ).…”
Section: Differentiation Of Mscsmentioning
confidence: 99%